2010
DOI: 10.1245/s10434-009-0891-9
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G Expression in Human Breast Cancer: Implications for Diagnosis and Prognosis, and Effect on Allocytotoxic Lymphocyte Response After Hormone Treatment In Vitro

Abstract: Our findings suggest that HLA-G may have potential clinical implications in diagnosis, prognosis, and immunotherapy of patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 28 publications
8
89
2
1
Order By: Relevance
“…24,25 Also, breast cancer patients with HLA-G-positive expression had a shorter disease-free survival time. 28 Other studies also revealed that there was significant correlation between HLA-G expression and poor clinical outcomes in lung, gastric and colorectal tumors. 26,31,32 In the context of ESCC, a previous study revealed that HLA-G was expressed in 90.9% (110/121) of the primary sites of ESCC, which is much higher than that observed in our study (65.8%, 52/79).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…24,25 Also, breast cancer patients with HLA-G-positive expression had a shorter disease-free survival time. 28 Other studies also revealed that there was significant correlation between HLA-G expression and poor clinical outcomes in lung, gastric and colorectal tumors. 26,31,32 In the context of ESCC, a previous study revealed that HLA-G was expressed in 90.9% (110/121) of the primary sites of ESCC, which is much higher than that observed in our study (65.8%, 52/79).…”
Section: Discussionmentioning
confidence: 97%
“…43 In our study, no correlation was found for the sHLA-G in plasma with clinicopathological parameters in ESCC patients. Similarly, no clinical significance for the sHLA-G was also observed in other malignancies such as breast cancer and renal cell carcinoma, 28,44 raising the hypothesis that the clinical relevance of sHLA-G is tumor type dependent and varies among different types of malignancies.…”
Section: Tumor Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…Among these studies, there is a high frequency of tumor cell-surface HLA-G expression with an absence in healthy tissue, and increased sHLA-G levels has been detected in various body fluids in a variety of cancers (14). Expression of HLA-G was found to be correlated with clinical parameters such as more advanced disease stage, tumor metastasis and/or with a worse prognosis in tumor patients, indicating that HLA-G could facilitate tumor immune escape, invasiveness and metastasis; thereby HLA-G expression was found to be associated with advanced clinical stage and disease progression and HLA-G expression was also documented as an unfavorable prognostic factor for many kinds of solid malignancies, including breast cancer (59)(60)(61)(62)(63)(64), colorectal cancer (65,66), cervical cancer (67,68), endometrial of allogeneic skin graft survival (52). In an immunocompetent HLA-G1 + M8…”
Section: Relevance Of Hla-g Expression In Cancersmentioning
confidence: 99%
“…1E-F); these results agree with those previously reported. 23 However, de Kruijf et al published that HLA-G expression had no significant prognosis correlation in breast cancer. 17 This discrepancy could be due to differences in the classification method of HLA-G expression.…”
Section: Discussionmentioning
confidence: 99%